2013
DOI: 10.2105/ajph.2012.300846
|View full text |Cite
|
Sign up to set email alerts
|

Access to Oral Health Care: The Role of Federally Qualified Health Centers in Addressing Disparities and Expanding Access

Abstract: These results underscore the critical role that health centers play in national efforts to improve oral health status and eliminate disparities in access to timely and appropriate dental services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…Individuals who were female, married, native speakers, living in a metropolitan statistical area, and with dental insurance were also associated with increased utilization of general dental care. Although we studied different populations and different time periods, our results mirrored those of previous researches documenting striking racial/ethnic disparities in access to dental health care [13,[25][26][27], except one study conducted by Jones and her colleagues in 2013, using the 2009 Health Center Patient Survey [21]. They examined utilization, unmet need, and satisfaction with oral health services among Federally Qualified Health Center patients, and found no racial or ethnic disparities in access to oral health care.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Individuals who were female, married, native speakers, living in a metropolitan statistical area, and with dental insurance were also associated with increased utilization of general dental care. Although we studied different populations and different time periods, our results mirrored those of previous researches documenting striking racial/ethnic disparities in access to dental health care [13,[25][26][27], except one study conducted by Jones and her colleagues in 2013, using the 2009 Health Center Patient Survey [21]. They examined utilization, unmet need, and satisfaction with oral health services among Federally Qualified Health Center patients, and found no racial or ethnic disparities in access to oral health care.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, among the ample evidences in the evaluations of US adults showing a significant gap between non-Hispanic whites and other racial/ethnic groups [17][18][19], most of these studies, however, concentrated only on generalized health care services, and evidences on dental care services were either limited or based on summary statistics. There have been studies even suggesting that minorities may in fact have similar or better access to care relative to non-Hispanic whites [9,[20][21].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Investigators in a recent study found that there were no racial or ethnic disparities in dental care utilization among FQHC patients, suggesting that these facilities may function as a critical access point to oral health services in disadvantaged communities. 21 The federal statute under which FQHCs receive grants requires all of these facilities to provide preventive dental services either on site or by means of referral. According to the American Dental Association, 22 75 percent of FQHCs provided on-site dental services in 2009.…”
mentioning
confidence: 99%
“…38 Although 75 percent of the funded health centers provided some on-site dental care, many have multiple sites and do not necessarily provide dental services at all locations. 39 Future studies should examine whether the centers reduce dental ED visits among Medicaid beneficiaries in areas where the supply of dental providers, particularly those who accept Medicaid, is low.…”
Section: Discussionmentioning
confidence: 99%